E-Justice 2009
DOI: 10.4018/978-1-59904-998-4.ch002
|View full text |Cite
|
Sign up to set email alerts
|

E-Justice and Policies for Risk Management

Abstract: In spite of the technological, economic, and normative efforts, all democratic countries are developing electronic filing (e-filing) in the justice sector, but only a few of them have operational systems. This chapter tries to give a solution to this situation in light of risk management theories. Different strategic approaches to policies for risk management have been adopted by institutions governing ICT technologies in the development of the judicial electronic data interchange (JEDI). As the author shows w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In particular, the several services (from divorce management to health services), the technical components (the more sophisticated technology adopted), the legislation (the rules that need to be changed and adopted), the organization (number and level of the subjects involved), and the institutional level (involvement of many sectors of the public administration) have been modified in such a way to increase the system's complexity dramatically, making it difficult to achieve a new alignment. The project's ex-cessive complexity was one of the main reasons for the failure of e-justice projects in several national contexts (Carnevali 2010;Contini and Lanzara 2014;Lupo 2014;Carnevali 2009).…”
Section: Protagonists Of Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the several services (from divorce management to health services), the technical components (the more sophisticated technology adopted), the legislation (the rules that need to be changed and adopted), the organization (number and level of the subjects involved), and the institutional level (involvement of many sectors of the public administration) have been modified in such a way to increase the system's complexity dramatically, making it difficult to achieve a new alignment. The project's ex-cessive complexity was one of the main reasons for the failure of e-justice projects in several national contexts (Carnevali 2010;Contini and Lanzara 2014;Lupo 2014;Carnevali 2009).…”
Section: Protagonists Of Innovationmentioning
confidence: 99%
“…Projects that are developed from a bottom-up approach-such as COLLEGA and ANTHEA-are sensibly affected by growing size and complexity (Maeda 2006). The more the creators' manage to stay focused, the more they can have a chance of success; yet, the more they expand, the more they risk getting out of control and failing (Carnevali 2019(Carnevali , 2009. Several European experiences of e-justice system development provide examples of failures related to the lack of attention posed by developers to comply with the so-called "maximum manageable complexity" (Contini and Lanzara 2014).…”
Section: Protagonists Of Innovationmentioning
confidence: 99%
“…Therefore, to indicate equal citations, fields like title of report, year, volume, page number and court are given. A study by Carnevali (2008) found that majority of countries are developing electronic case filing (e-filing) systems in the judiciary. Interestingly, only a few systems are appropriate and functional.…”
Section: Judicial Documents Metadatamentioning
confidence: 99%
“…In the last twenty years (Fabri and Contini 2001, Plotnikoff and Woolfson 2001, Kujanen and Sarvillina 2001, Wallace 2003, Carnevali 2009, Reiling 2009, 2010, Kallinikos 2009, Fabri 2004, CEPEJ 2016, CEPEJ 2017, CEPEJ 2019a, 2020a, European Union Commission 2020a), judicial systems have invested quite a lot of money in developing ICT infrastructures and applications. The main investments in applications can be summarised in four broad areas: 1) case law; 2) digitising case processing (i.e.…”
mentioning
confidence: 99%